2021
DOI: 10.1039/d1cc03539h
|View full text |Cite
|
Sign up to set email alerts
|

Double-headed nucleic acids condense the molecular information of DNA to half the number of nucleotides

Abstract: Nucleotide monomers that hold two nucleobases each, i.e. double-headed nucleotides, have been shown to form two sets of functional Watson–Crick base pairs when incorporated into dsDNA, and they hereby behave...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Also, the discrimination of almost all mismatches is excellent as they range from 8.0-16.0 °C [21][22][23][24] with the only exceptions being the D•C of U D (5.5 °C) [23] and ClU•G of U ClU (3.0 °C). In this context we are convinced that the poor discrimination of T•G mismatches that was also found for our previous A T and G T monomers (1.5-3.0 °C) [24,25] can be improved as well by the replacement of thymine with 5-chlorouracil.…”
Section: Hybridization Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…Also, the discrimination of almost all mismatches is excellent as they range from 8.0-16.0 °C [21][22][23][24] with the only exceptions being the D•C of U D (5.5 °C) [23] and ClU•G of U ClU (3.0 °C). In this context we are convinced that the poor discrimination of T•G mismatches that was also found for our previous A T and G T monomers (1.5-3.0 °C) [24,25] can be improved as well by the replacement of thymine with 5-chlorouracil.…”
Section: Hybridization Studiessupporting
confidence: 70%
“…Recently, we have focused on C2' functionalized double-headed arabinonucleotides with methylene-linkers (U X , Figure 1A), as they can form WatsonÀ Crick base pairs with both nucleobases and thereby act as condensed dinucleotides in a DNA duplex. [20][21][22][23][24][25][26] Encouragingly, molecular dynamics studies have shown that local adjustments of the backbone counteract the structural alteration induced by the incorporation of a double-headed nucleotide, so that the overall B-type duplex of DNA is retained. [23] Moreover, the thermal duplex stability is not particularly affected (� 4.0 °C) [20][21][22][23][24][25] when dinucleotides are replaced with the corresponding double-headed nucleotides.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18−20 Multiple incorporations in both strands of the duplex are also tolerated, 19 and even fully modified 5-mers have been shown to form double-headed nucleic acid duplexes with increased stability (+27.0 °C) compared to the 10-mer DNA reference duplex with the same nucleobase sequence. 20 As the monomers display efficient mismatch discrimination on both nucleobases, double-headed nucleotides effectively function as condensed dinucleotides in dsDNA. In contrast, notable reductions in the thermostabilities of 3.5−10.5 °C were observed for DNA•RNA duplexes containing the B X monomers.…”
Section: ■ Introductionmentioning
confidence: 99%